Fibrillarin binds directly and specifically to U16 box C/D snoRNA. - Fatica, A (2000)
Eukaryotic nucleoli contain a large family of box C/D small nucleolar ribonucleoprotein complexes (snoRNPs) that are involved in processing and site-specific methylation of pre-rRNA. Several proteins have been reported to be common factors of box C/D snoRNPs in lower and higher eukaryotes; nevertheless none of them has been clearly shown to directly interact with RNA. We previously identified in Xenopus laevis, by means of UV crosslinking in vivo, two proteins associated with box C/D snoRNAs, fibrillarin and p68. Here we show that fibrillarin interacts directly and specifically with the U16 box C/D snoRNA in a X. laevis oocyte nuclear extract and that it does not require p68 for binding. Specific binding is also obtained with a recombinant fibrillarin demonstrating that the protein is able to bind directly and specifically to U16 snoRNA by itself.